Essential Oils in Broiler Nutrition - Lee, K.-W.; Everts, H.; Beynen, A.C. (International Journal of Poultry Science, 2004)
Based on literature data it can be concluded essential oils originating from plants have anti-microbial activity and have toxic effects in poultry only when administered at very high doses. Antioxidant activity and hypocholesterolemic effects have been reported in chickens. In various studies, but not all, a growth enhancing effect of essential oils has been found. The characteristic flavor of essential oils might play role in poultry performance, but this needs to be confirmed. Essential oils may stimulate the digestion process. It appears that individual compounds of an essential oil have a wide range of activities and may act in an additive, synergistic and antagonistic fashion. The effect of essential oils in poultry may not only be confined to the microflora, but may extend to animal metabolism. Knowing the activity and effects of individual compounds is useful to formulate mixtures of compounds so as to enhance efficacy. In conclusion, dietary essential oils may be used as alternatives to antibiotics, but whether their effects on growth performance are a consequence of anti-microbial activity needs to be studied further.